2021
DOI: 10.1111/jar.12911
|View full text |Cite
|
Sign up to set email alerts
|

The impact of nutrition on sleep in people with an intellectual disability: An integrative literature review

Abstract: Background People with intellectual disabilities are more likely to experience sleep problems. Sleep can impact on health and well‐being; therefore, evidence‐based interventions are required to improve sleep in this population. Method An integrative literature review was conducted on the impact of nutrition on sleep in people with intellectual disabilities. Following screening of papers (n = 289), 14 papers met the inclusion criteria. Results Themes related to nutrition and improved overall well‐being, use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Moreover, a study with atrial fibrillation patients, with mean age 68 years, found that as sleep quality worsened (according to PSQI), malnutrition risk (according to MNA) increased [ 64 ]. Moreover, nutritional interventions may improve sleep quality in people with intellectual disabilities [ 65 ]. Dietary patterns seem to be an important factor to improving the quality and quantity of sleep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a study with atrial fibrillation patients, with mean age 68 years, found that as sleep quality worsened (according to PSQI), malnutrition risk (according to MNA) increased [ 64 ]. Moreover, nutritional interventions may improve sleep quality in people with intellectual disabilities [ 65 ]. Dietary patterns seem to be an important factor to improving the quality and quantity of sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary patterns seem to be an important factor to improving the quality and quantity of sleep. However, the current literature regarding the benefit of improved nutrition on sleep in people with an intellectual disability needs to be interpreted with caution [ 65 ].…”
Section: Discussionmentioning
confidence: 99%